Association Between Peripheral Blood Levels of Vitamin A and Autism Spectrum Disorder in Children: A Meta-Analysis - Wang, Ni; Zhao, Yuqian; Gao, Junwei (Frontiers in Psychiatry, 2021)
Vitamin A is an essential fat-soluble micronutrient that plays important roles in a surprisingly wide variety of biological processes from early growth and development to brain maintenance. Numerous clinical studies have been conducted to explore the relationship between peripheral vitamin A levels and autism spectrum disorder (ASD), but the results of these studies are controversial. Therefore, we assessed the association between peripheral vitamin A levels and ASD in the present meta-analysis. Relevant records were retrieved through the Embase, Web of Knowledge and PubMed databases up to 13 November 2020. Reference lists were also searched and analyzed. Hedges’ g with its corresponding 95% confidence interval (CI) was used to assess the association between peripheral vitamin A levels and ASD. A fixed or random effects model was selected according to a heterogeneity test in overall and subgroup analyses. Five records (six studies) with 935 ASD children and 516 healthy children were included in the present study. Significantly decreased peripheral vitamin A concentrations were observed in ASD children compared with healthy children (Hedges’ g= -0.600, 95% CI -1.153 to -0.048, P=0.033). A similar result was also obtained after removing the studies identified by Galbraith plots. In addition, no obvious publication bias was found in the meta-analysis. The findings of our meta-analysis suggested decreased peripheral vitamin A levels in ASD children compared with healthy children. Further investigations into the effects of vitamin A on the development of ASD are warranted.